AMIGA at the Pierre Auger Observatory: The interface and control electronics of the first prototype muon counters - Videla, M. (2015)
AMIGA is an enhancement of the Pierre Auger Observatory. The main goals of AMIGA are to extend the full efficiency range to low erenergies of the Observatory and to measure the muon content of extensive air showers. Currently, it consists of 61 detector pairs, each one composed of a surface water-Cherenkov  detector and a buried muon counter. Prototypes of the muon counter ? buried at a depth of 2.25m ? were installed at each vertex of a hexagon and at its center with 750 m spacing. Each prototype has a detection area of  10m**2 segmented in 64 scintillation strips and coupled to a multi-anode PMT through optical fibers. The electronic systems of these prototypes are accessible via a service tube. An electronics interface and control board were designed to extract the data from the counter and to provide a remote control of the system. This article presents the design of the interface and control board and the results and performance duringthe first AMIGA acquisition period in 2012.